Design and Implementation of a Musical System for the Development of Creative Activities Through Electroacoustics in Educational Contexts - Esteban Peris; Adolf Murillo; Jesús Tejada (Signals, 2025)
In the field of music education, the incorporation of technology originally designed for professionals presents both significant opportunities and challenges. These technologies, although advanced and powerful, are often not adapted to meet the specific needs of the educational environment. Therefore, this study details the design and implementation process of a system consisting of a hardware device called “Play Box” and associated software “Imaginary Play Box”. The design sciences research methodology (DSRM) specifically adapted to software development was used to structure the project. The three phases shown in this study ranged from the conception of an initial prototype to the realisation of working software. During the design phase, a questionnaire was developed to evaluate various aspects of the software, such as the visual interface, the programming of components, and the sound interactivity provided by the Play Box. The technique of panels of experts in music pedagogy and programming in MAX-MSP was used to obtain critical feedback. This expert evaluation was crucial to iterate and polish the process of iteration and refining the software, culminating in a beta version optimised for the creation of electroacoustic music for music education.